DEVELOPMENT OF MOBILE MARKETING IT PROJECTS: OPPORTUNITIES FOR MOLDOVA AND UKRAINE - CHAIKOVSKA, Maryna; LEVITSKAIA, Alla (Economy and Sociology, 2021)
This article describes the main problematic issues and modern approaches to managing and developing mobile marketing IT projects. In this study, the authors set the goal of the study – to analyze the features of IT project management in mobile marketing, to systematize the development models of modern web projects and to study the possibilities of using flexible applied methodologies that formalize the development and modification of web applications based on the use of effective methods for managing IT projects in mobile marketing. To achieve this research goal, the authors used theoretical and conceptual analysis, studied existent empirical databases for the mobile application market in the Republic of Moldova and Ukraine. The authors highlighted the critical problems of using agile methodologies in IT projects of mobile marketing. A comparative analysis of the feature’s applicability of IT project management methodologies and problems of their using in mobile marketing applications are presented. The logical and structural diagram of the stages of the Mobile App Design Timeline is proposed, which contributes to increasing the effectiveness of the implementation of information technology projects in general. To assess the applicability of the flexible methodologies of Kanban and Scrum, an IT project of mobile marketing was simulated. The significance of the results obtained is predetermined by the fact that they could form a theoretical base for improving the effectiveness of marketing activity under conditions of the informatization of society through the building a selforganizing team and use of agile methodologies in mobile marketing IT projects.